PEMBERDAYAAN KWT DESA KRANGGAN DALAM BUDIDAYA PADI DENGAN METODE S.R.I. UNTUK PERTANIAN SEHAT - Agung Astuti; Mulyono Mulyono (Universitas Muhammadiyah Surakarta, 2019)
The main problem of rice production in Kranggan village is mainly due to the lack of water, low soil fertility, high cost of seeds and fertiliser, which resulted in small output despite the overuse of synthetic fertilisers. In this activity, we described the accompaniment and application of SRI method for rice cultivation, particularly for the women farmer’s group. This community service aimed to improve the knowledge, insight, and skill in rice cultivation by employing SRI method to save the water, reduce the cost of seeds and fertiliser, and increasing time efficiency in rice production. It was anticipated that such an approach would result in the environmentally friendly production of healthy rice. The activity of community service was based on a survey to analyse the agricultural status of Kranggan village, extension activity on the application SRI method for rice cultivation, practical training and demonstration of rice cultivation plot using SRI method, and healthy rice packaging by the members of Women Farmer’s Group. The activities were then followed by pre-test and post-test to confirm the improvement of knowledge and skill. The results of the community service demonstrated that the use PowerPoint method for knowledge delivery increased the understanding of SRI system by 89%, while direct training in organic NPK fertiliser production and seagrass POC increased the skill by 85%. Besides, the accompaniment of the Women Farmer’s Group up to the post-harvest period empowered the group members as the rice production was environmentally friendly, lowered the cost, reduced the use of water and labour cost, resulted in the production of healthy rice, and increased selling price by 50%. Keywords: System of Rice Intensification, the Women Farmer’s Group Kranggan